Summary Guidance Note — IOM’s post-flood reconstruction intervention in Mirpurkhas, Sindh, Pakistan: Examining contributions to resilience across the Humanitarian-Development-Peace Nexus - Khalid, Shahab; Vaselli, Alessandra; Savelli, Adam; Craparo, Alessandro; Basel, Ashleigh; Minoarivelo, Henintsoa Onivola; Tsoka, Jonathan; Dao, Hoa; Khan, Muhammad; Boase, Edward Jago; Badar, Mohsin; Mastrorillo, Marina; et al. (2025)
This Summary Guidance Note outlines key results and recommendations from the Full Report. The CGIAR Science Program on Food Frontiers and Security’s partnership with the International Organization for Migration (IOM) aims to identify technical entry points for strengthening climate action interventions. In 2022, compounding climate and environmental factors contributed to extreme rainfall and flooding across Pakistan, affecting 33 million people, damaging 2.1 million homes, and displacing more than seven million people across 30 districts, including 27 in Sindh. In response to flood-related displacement and damage to homes and infrastructure, IOM initiated a pilot intervention to rebuild homes, construct pour-flush latrines and hand-powered water-pumps, and, in some villages, develop additional community infrastructure. Methods consist of a quantitative mapping of baseline (current) and projected climate hazards (by 2040), an n = 459 survey of intervention participants, several weeks of field observation, and key informant interviews were the household participants, community leaders, IOM staff, and IOM’s implementing partners. Results show that: climate hazards will worsen in Mirpurkhas by 2040; by improving households’ reported environmental security, IOM’s intervention enhanced households' subjective resilience to anticipate, withstand, recover from, and transformatively adapt to future hazards; the provision of durable housing enhanced economic security; smaller households require additional support to achieve equitable resilience improvements; the intervention’s WASH components had a positive effect on women’s subjective resilience; by devolving some decision-making power to household participants during local implementation, the intervention improved household agency, supported community-led development, and boosted social cohesion in target villages.